Kelas Ibu Hamil : Teman Setia Menuju Persalinan Bahagia - Apriliana Pipin; Telly Katharina; Intanwati Intanwati; Trivina Trivina; Agnes Dwiana Widi Astuti (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
A common problem faced by the community is the low level of knowledge among pregnant women regarding the importance of regular prenatal checkups, balanced nutrition, prenatal exercise techniques, mental preparation, and warning signs during pregnancy. This condition can increase the risk of complications that endanger the mother and fetus. To address this issue, the "Pregnancy Class: A Loyal Friend Towards a Happy Childbirth" program was implemented, which aims to improve the knowledge, skills, and preparedness of pregnant women for a healthy and comfortable delivery. This program was implemented through several methods, namely pre- and post-tests to measure the level of participant understanding, health education by professionals, and mentoring in prenatal exercise practice. The counseling materials included the importance of regular prenatal checkups, proper nutritional fulfillment, early detection of pregnancy warning signs, and mental and emotional strengthening of pregnant women. The results of the activity showed that this program had a positive impact. The average knowledge score of pregnant women increased from 60 in the pre-test to 90 in the post-test. In addition, participants showed consistent attendance and high enthusiasm throughout the session. The prenatal exercise activity ran smoothly, with active participation from participants who felt more relaxed and comfortable, especially in the waist area. In conclusion, this program successfully increased the preparedness and confidence of pregnant women facing childbirth. The implication of this activity is the importance of implementing regular and ongoing prenatal classes with the support of village midwives, health workers, and families to reduce the risk of complications and improve the well-being of mothers and babies.